Impact of respiration on stroke volumes in paediatric controls and in patients after Fontan procedure assessed by MR real-time phase-velocity mapping. (22nd September 2014) - Körperich, Hermann; Barth, Peter; Gieseke, Jürgen; Müller, Katja; Burchert, Wolfgang; Esdorn, Hermann; Kececioglu, Deniz; Beerbaum, Philipp; Laser, Kai Thorsten
Abstract: Aims: Blood flow rate quantification using two-dimensional phase-contrast MRI (PC-MRI) results in averaging of flow information due to long acquisition times precluding the examination of short-term effects. The aim of this study was to determine respiration-related flow rate variations by non-electrocardiographic triggered real-time phase-contrast MRI (PC-MRI). Methods and results: Real-time PC-MRI was applied to study respiration-driven blood flow fluctuations in the ascending aorta (AAo), superior vena cava (SVC), and inferior vena cava (IVC) under normal and forced breathing in 33 healthy children and 10 Fontan patients. Respiration-dependent flow rates were virtually generated by dividing the respiration curve into four segments: expiration, end-expiration, inspiration, and end-inspiration. Whereas in volunteers aortic flow rate was elevated during end-expiration (5.6 ± 3.0%) and decreased during end-inspiration (−5.8 ± 3.5%) in relation to mean blood flow ( P < 0.05), highest flow was detected during inspiration in SVC (10.5 ± 14.1%) and IVC (22.5 ± 12.1%) and lowest flow during expiration (−11.6 ± 13.5%, −13.2 ± 14.1%, P < 0.05). Differences were increased under forced breathing in AAo (10.4 ± 5.5%, −7.4 ± 6.5%, P < 0.05) and SVC (40.0 ± 30.3%, −30.0 ± 19.2%, P < 0.05), whereas were unchanged in IVC (16.5 ± 23.6%, −13.7 ± 21.6%, P = n.s.). Regarding patients, respiratory-dependent flow rate variability was increased and had to be related to the patient's individual quality of Fontan circulation. Conclusion: Real-time PC-MRI allows a physiological assessment of respiratory-related flow rate fluctuations in healthy subjects as well as in Fontan patients. Its capability for detection of short-term effects in clinical routine was demonstrated.